Conversion of Apricot Kernel Oil into Biodiesel Using Alkaline Catalysts (Latakia University Journal -Basic Sciences Series, 2024)
Biodiesel is a clean - burning alternative fuel source that can be produced from animal fats, vegetable oils, and algae oil. This research deals with the production of biodiesel from apricot seeds oil, which is a rich source of oil. The oil was extracted from apricot seeds by maceration using n-hexane as a solvent. Biodiesel was prepared by the alkaline catalyzed transesterification method, and the reaction yield reached 86.3 % at the reaction conditions: molar ratio of oil: methanol ( 1:6 mol/mol), the amount of catalyst (0.5 wt % of the weight of the oil), reaction temperature 65 °C over 90 minutes.  the physical and chemical properties of the prepared biodiesel were studied , and they confirmed the American (ASTM) and European (EN) Standards. In addition, The combustion test of the prepared biodiesel was carried out and the results were discussed.